2020
DOI: 10.1097/01.ogx.0000688044.66625.e4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Pregnancies With a Confined Placental Mosaicism and Implications for Prenatal Screening Using Cell-Free DNA

Abstract: (Abstracted from Genet Med 2020;22:309–316) The most common type of confined placental mosaicism (CPM), the presence of a chromosomal abnormality in the placenta but not in the fetus, involves trisomy/disomy. Confined placental mosaicism occurs in 97% of rare autosomal trisomy (RAT) cases detected by chorionic villus sampling (CVS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The presence of confined placental mosaicism could explain a positive NIPS result for rare aneuploidy and results in a high discordance rate between NIPS and invasive diagnosis by amniocentesis. Notably, confined placental mosaicism for RAT is not associated with an increased risk of fetal anomalies and pregnancy complications, as compared to cases with a normal karyotype on invasive diagnosis by CVS 25 . Therefore, when rare aneuploidy is reported by NIPS, the specimen source for invasive diagnostic testing should be considered carefully and caution should be taken when interpreting results from CVS or placental studies 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of confined placental mosaicism could explain a positive NIPS result for rare aneuploidy and results in a high discordance rate between NIPS and invasive diagnosis by amniocentesis. Notably, confined placental mosaicism for RAT is not associated with an increased risk of fetal anomalies and pregnancy complications, as compared to cases with a normal karyotype on invasive diagnosis by CVS 25 . Therefore, when rare aneuploidy is reported by NIPS, the specimen source for invasive diagnostic testing should be considered carefully and caution should be taken when interpreting results from CVS or placental studies 3 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that mosaicisms from CVS should be further verified for TFM by AF or CB due to the presence of fetoplacental discrepancies 19 . However, although most pregnancies diagnosed with CPM are deemed to have good postnatal outcomes but an impaired placenta may provide insufficient support for the pregnancy, leading to foetal complications such as FGR or other adverse outcomes 20,21 . Therefore, continuous monitoring of foetal growth during pregnancy is important to prevent adverse complications for foetuses with TFM and CPM.…”
Section: Discussionmentioning
confidence: 99%
“…A major known cause of placental insufficiency in a viable pregnancy is confined placental mosaicism (CPM), where some or most cells in the placenta are aneuploid, while the fetus has a predominantly normal diploid chromosome complement. CPM identified prenatally is associated with increased risk for FGR and other pregnancy complications depending on the levels of abnormal cells and the chromosome(s) involved (Robinson et al 1997;Grati et al 2019). Screening placentas postnatally has also confirmed a contribution of CPM to FGR (Artan et al 1995;Krishnamoorthy et al 1995;Wilkins-Haug et al 1995;Stipoljev et al 2001).…”
Section: Introductionmentioning
confidence: 99%